The Relationship Level of Knowledge of Students in Class XI High School about Sexually Transmitted Infections (STI) with Adolescent Sexual Behavior at SMA GKPS Pematang Raya - Nurmala; Daulay, Dewi Wandha Syahputri (International Journal of Public Health Excellence (IJPHE), 2023)
Knowledge is the result of human sensing, or the result of knowing someone about an object through their senses (eyes, nose, ears, etc.). By itself, at the time of sensing to produce knowledge is strongly influenced by the intensity of attention and perception of the object. Adolescence is a period of rapid growth and development both physically, psychologically and intellectually. It is typical for adolescents to have a great sense of curiosity, like adventure and challenges and tend to be willing to take risks for their actions without being preceded by a mature balance. This uses a quantitative descriptive design. Nursalam (2008), descriptive research aims to describe (describe) important events that are happening today. The number of samples used was the GKPS Pematang Raya students totaling 40 people. The results of the study showed that the majority of respondents aged 14-15 years were 28 people (70? ), while the respondents aged 16 were 14 people (306). the gender of the male and female respondents was the same, namely 20 men (50Y4) and 20 women (50%). However, in general, women who experience anxiety more often have a good level of knowledge about sexually transmitted diseases, namely 26 respondents (65%). The level of knowledge of adolescents about sexually transmitted diseases is less than 14 respondents (35%). It is recommended that students add more insight into their knowledge of sexually transmitted diseases, so that teenagers are even more aware of sexually transmitted diseases and hold counseling about sexually transmitted diseases in adolescents so that their knowledge increases.